1997
DOI: 10.1002/aic.690430525
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic behavior of fluidized beds based on pressure and voidage fluctuations

Abstract: Absolute and differential fluctuations and local voidage fluctuations are commonly used in characterizing gas-fluidized beds. Pressure fluctuations can result from several different causes including bubble formation and eruption, selfexcited oscillations of fluidized particles, pressure oscillations in the plenum chamber due to piston-like motion of the bed, bubble coalescence, and bubble splitting (Bi et al., 1995). Pressure waves from these sources can be propagated through the emulsion phase, although the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 24 publications
4
51
0
Order By: Relevance
“…These methods are based on the analysis of ε G data. Other flow regime identification methods are the fractal [319], wavelet [320,321], Hurst's [322,323], spectral and nonlinear chaos [93,320,[324][325][326][327][328][329][330][331][332][333] and Kolmogorov entropy [332][333][334] approaches. Some authors have used methods based on the Shannon entropy, which measures the degree of indeterminacy in a system [335,336].…”
Section: The Flow Regimesmentioning
confidence: 99%
“…These methods are based on the analysis of ε G data. Other flow regime identification methods are the fractal [319], wavelet [320,321], Hurst's [322,323], spectral and nonlinear chaos [93,320,[324][325][326][327][328][329][330][331][332][333] and Kolmogorov entropy [332][333][334] approaches. Some authors have used methods based on the Shannon entropy, which measures the degree of indeterminacy in a system [335,336].…”
Section: The Flow Regimesmentioning
confidence: 99%
“…Advanced statistical analysis tools such as chaotic and wavelet analyses have also been applied to the pressure fluctuation signals to improve the understanding of their complexity. It was shown (Bai et al, 1997;Zhao and Yang, 2003) that two correlation dimensions could be identified in both absolute and differential pressure signals, with the higher dimension being speculated as originating from the small-scale signals associated with particle movement and the lower dimension from large-scale signals associated with bubble motion. The existence of pressure waves and bed oscillations will definitely further complicate the interpretation of those correlation dimensions.…”
Section: Decoupling Of Pressure Fluctuations In Gas-solid Fluidized Bedsmentioning
confidence: 99%
“…Different analytical methods, including statistical or correlation methods, powerspectral density, deterministic chaos, and the Wigner distribution have been used (e.g. Fan et al, 1990;Kage et al, 1991;Bai et al, 1997;He et al, 1997;Briens et al, 1997a,b;Ohara et al, 1999;Briens and Briens, 2002;Chaplin et al, 2004Chaplin et al, , 2005. However, the application of these methods in spouted beds is scarce, with only a few attempts reported in the literature (Wang et al, 2001;Freitas et al, 2004;Xu et al, 2004a,b,c;Piskova and Morl, 2007).…”
Section: Introductionmentioning
confidence: 99%